2002
DOI: 10.1021/la011152q
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Study of the SAMs of 6-Mercaptopurine (6MP) at Hg and Au(111) Electrodes in Alkaline Media

Abstract: A study of the reductive desorption process of 6MP-coated Hg and Au(111) electrodes in alkaline media has been carried out by means of such electrochemical techniques as cyclic voltammetry, chronoamperometry, and capacity−potential curves. The cyclic voltammograms show a single reduction peak whose peak potentials are strongly dependent on the nature of the substrate, Hg and Au(111) in this study. The full widths at half-maximum (fwhm) for Hg and Au(111) electrodes respectively are 19 and 21 mV at a scan rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…Scheme 2 can be proposed for the arrangements of the rows of stacked 6TG molecules. For the 6MP-SAM formed in mercury, a different orientation has been proposed [13], consisting of the interaction of the N1 with the mercury surface, in addition to the covalent SHg bond. The interaction of the nitrogen atoms in the ring with the electrode surface could not be established by electrochemical means alone, but has been observed for 6MP chemisorbed at a silver electrode by surface enhanced Raman spectroscopy [24].…”
Section: General Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 2 can be proposed for the arrangements of the rows of stacked 6TG molecules. For the 6MP-SAM formed in mercury, a different orientation has been proposed [13], consisting of the interaction of the N1 with the mercury surface, in addition to the covalent SHg bond. The interaction of the nitrogen atoms in the ring with the electrode surface could not be established by electrochemical means alone, but has been observed for 6MP chemisorbed at a silver electrode by surface enhanced Raman spectroscopy [24].…”
Section: General Studymentioning
confidence: 99%
“…Recent studies of SAMs on mercury have shown that highly organized, two-dimensional arrays of adsorbed molecules are obtained [6][7][8][9][10][11][12][13]. Demoz and Harrison [6] reported on the formation of an extremely impermeable, low-defect density hexadecanethiol monolayer on mercury.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, interactions among aromatic rings (which are of the π → π stacking type) are stronger than those among aliphatic chains. For this reason (and also due to the rigidity of such rings), a densely packed SAM of 6-mercaptopurine (6MP) is formed on Hg in spite of the small size of its constituent molecules, as reported in several publications [26][27][28][29].…”
Section: Introductionmentioning
confidence: 93%
“…Other interesting features, which are out of the scope of this chapter, about the reductive desorption of organothiolate SAMs from a metal surface include the micelle-like aggregates that are formed after the desorption [11,12,25,71], the appearance of multiple peaks on the n voltammogram [9,31,33,72], the effects of pH [44], the reoxidative adsorption after the desorption [11,[73][74][75], the effect of the nature of the metal and the facets on SAMs [10,19,[76][77][78][79], the role of solvents used for the formation of SAMs [27,80], the effect of the type of ω-terminal on the desorption behavior [3,14,34,38,81], the rate of the ion penetration [1], the effect of the temperature on the shape of voltammograms [82], and the desorption of SAMs other than alkanethiols [23,24,32,49,50,53,[83][84][85][86].…”
mentioning
confidence: 99%